(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Hemophilia is the most common serious congenital coagulation factor deficiencies. The prevalence of hemophilia is estimated to be about 1:10,000 birth and that of the severe form of the disease to be about 6% per 1,00,000 population. The most pathetic part of this disease is that even medical personnel are sometimes not familiar with its diagnosis and management. There is obviously a need to establish facilities and treatment options that will help the patient with hemophilia to manage their life with ease. As this is a genetic disorder no complete cure is possible as of now. The only available treatment option is the infusion of factors and some adjuvant therapies depending upon the bleeding conditions .Hemophilia, if not properly managed, can lead to chronic disease and lifelong disabilities. The challenges and issues in infants/young children are different from those in older children and adults although episodes of bleeding still predominate as the diagnostic trigger. Currently, inhibitor development is a challenging complication of pediatric hemophilia and prophylaxis is emerging as the optimal preventive care strategy. In this section we will review some important aspects of hemophilia in children including early prophylaxis, current evidence relating to inhibitor development. J. Paediatr. Surg. Bangladesh 6(2): 54-63, 2015 (July)